Impact of Front Line Demonstrations on Mustard Crop in Sirsa District of Haryana - kumar, Sunil; Jakhar, Devender Singh (Indian Journal of Extension Education, 2021)
Krishi Vigyan Kendra conducts cluster demonstrations every year as per target assigned by ICAR. The study evaluates impact of 300 demonstrations on mustard crop in 120 hectare area conducted by KVK Sirsa since 2015-16 to 2017-18 in different villages of the district. The extension gaps in technologies were identified through farmers meetings and group discussions with the farmers. The findings indicated significantÂ increase in the average yield of demonstrated plot (15.13%) over the farmerâ€™s practice plot of mustard crop. Average yield of demonstration plots was recorded higher by 18.18 per cent, 14.09 per cent and 13.13 per cent in years 2015-16, 2016-17 and 2017-18, respectively. The extension gap was 4.0 q/ha, 3.10 q/ha and 2.89 q/ha while technology gap was 2.0 q/ha, 2.90 q/ha and 2.11 q/ha during consecutive years respectively. During these three years, yield increase in demonstration plots expressed as additional income over check plots accounted for Rs. 7670/ha, Rs. 12350/ha and Rs. 11590/ha respectively during various years.Â